Tendências de gastos com pessoal do Hospital Maria Aparecida Pedrossian: previsão com Séries Temporais - Carmem Borges Ortega (2024)
ORTEGA, Carmem Borges. Trends in personnel expenditures of the Maria Aparecida Pedrossian Hospital: a time series forecast. Master's Dissertation. School of Administration and Business – ESAN, Federal University of Mato Grosso do Sul – UFMS, Campo Grande, MS, Brazil. Advisor: Prof. Dr. Adriano Marcos Rodrigues Figueiredo. This work questions what is the trend in personnel expenditure of the Maria Aparecida Pedrossian University Hospital (Humap-UFMS/Ebserh) ? The main goal is to make an analysis of the trend in personnel expenses at the Humap using time series forecasts, focusing on the payroll from 2015 to 2022. Over decades, the evolution of strategic human resource management has brought a more strategic character essential for decision-making, actions, and organizational direction. Transformations, innovations, and quality of life in managing personnel expenses are increasingly characterized by processes that involve a series of challenges and opportunities. The impact of payroll expenses is associated with the management style adopted and the State's objectives in providing public goods. The research aims at the growing need to maintain transparency in the effective results of public spending to society. This study provides insights to hospital organization managers with economic and efficient mechanisms to explore the quality and improvement of services, aligned with the needs of the assisted population. A quantitative approach was used, analyzing the payroll reports from 2015 (the start of Ebserh's activities at Humap-UFMS) to 2022, to compute time series indicators, forecasting with a combination of statistical methods, which allow managers to make projections for new hires with negotiations with the Federal Government, based on patterns observed in historical data. The research data covered the payrolls and the sampling used in the study, specifically Personnel Expenses Statements (DDP) under the accounting classification 3.3190.11 - Fixed Salaries and Benefits - Civil Personnel, concerning the monthly payroll of salary items - CLT (00003), remuneration for trusted positions CLT (00269), commission position bonus - CLT (00301), and substitutions (00024), linked to the payroll for a time series. The data were extracted from SIAPE and the monthly data from SIGP Menthor, in nominal values expressed in the national currency. The forecast involved a combination of statistical forecasting methods (ETS, Theta, ARIMA, NNAR, TBATS, and STL). The dynamics of personnel expense performance at Humap, which began operations in 2015, were analyzed. As a result, a forecasting model for personnel expenses at Humap was obtained to support public policies in the personnel area, allowing managers to project new hires with negotiations with the Federal Government, based on historical data patterns to measure variability and model personnel quantity guidelines, so that these variations do not affect continuous actions that improve the public services provided to society daily, with a forecasting proposal for up to 24 months from the collected data. The use of these methods contributes to more accurate forecasting, based on research data that seeks to measure and understand variability more easily and to model personnel quantity guidelines, so that variations do not affect continuous actions that provide transformations, innovations, valuation, and improvement of public services provided to society. The data from the Theta method (the most accurate) estimate that by December 2024, the number of maturities will be around R$ 8,924,291.15. This means that: 1- employees must be more efficient in order to secure better raises; 2- there should be an increase in the hiring of employees at this level; 3- some relationship between items 1 and 2. A public policy based on personnel expenses must identify bottlenecks in service, according to a more in-depth analysis – quantitative data on specific positions and their salaries – to establish the proper balance between salary adjustments and workforce hiring. Talent retention becomes crucial, requiring the implementation of strategies that improve working conditions and encourage professionals to remain at the institution. Future projections for personnel expenses at the Maria Aparecida Pedrossian University Hospital (Humap) for the years 2023 and 2024 indicate moderate growth. This increase is consistent with trends observed in previous years and reflects the ongoing need for budget adjustments to accommodate new hires and salary increases. Human resource management will need to adapt to these changes, influencing strategic decisions about hiring, training, and personnel allocation. Keywords: Analysis of Time Series; Personnel Spending Trends; Public Health Policies, HUMAP; University Hospitals.